Analisis Strategi Manajemen Badan Amil Zakat Nasional Sibolga Berdasarkan Analisis SWOTt - Deny Yusmita; Amrizal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to evaluate the dominant internal and external factors affecting the effectiveness of managing Zakat, Infaq, and Sedekah (ZIS) at BAZNAS Sibolga. The research method involves SWOT analysis to identify Strengths, Weaknesses, Opportunities, and Threats in ZIS management. The analysis results indicate that Management Strengths and Operational Efficiency are the strongest internal aspects with a score of 92%, while Weaknesses such as Limited Resources and Inconsistent Implementation require more attention. To enhance effectiveness, Potential Collaborations and Government Support are considered key opportunities with scores of 100% and 85%, respectively. Threats such as Policy Changes and Competition need to be anticipated. In conclusion, optimizing Operational Efficiency with a focus on the collection and utilization of ZIS funds is key to improving community welfare and reducing poverty in Sibolga.